The Influenced of Steel Fiber in Hot Mix Asphalt Mixture to Enhance the Tensile Strength - Mohd Syukry, Safwan; Azizan, Muhammad Daniel Haiqal; Sobri, Muhd Salleh; Hazirah Bujang, (Multidisciplinary Applied Research and Innovation, 2024)
Deformation of the road was the main factor of the repeated loaded at high temperature to the asphalt pavements and one of the main distress mechanisms. Asphalt mixture incorporated with steel fiber to enhance the tensile strength would have investigated by used grade 60/70 of asphalt binder and 5% of optimum asphalt binder. The percentages of steel fiber that were used for the studied was 0, 1.2, 1.5, 2.1, 2.4% by total weight of aggregate. Purpose of this studied is to investigate the effect of steel fiber toward the asphalt mixture on improved the asphalt pavement. To decrease the road deformation and to compute the pavement cracked at incorporating steel fiber using Marshall Stability Test. The result from this study has shown that the mixture incorporating steel fibers for stability is decrease between control sample with 2.7% steel fiber which is 21.357 kN and 13.193 kN. The performance test due to stiffness analysis passed the requirement JKR, which is more than 2.6 kN/mm, even if the value of the steel fiber modified sample is lower than the control sample and it still relevance to implement.